Learn some basic skills and biomechanical variables for mini tennis players - SHIHAB, SHAYMAA SAMI (International Journal of Psychosocial Rehabilitation, 2020)
The advanced sports level reached by many countries is the direction of progress witnessed by the world in various scientific fields, which was clear in achieving sports achievements, which most countries used the best methods and training tools in the field of sports in order to bring the player to a high level in the performance of basic skills for any game, and since the goal of any coach in guiding efforts to achieve achievement was to use specialized training and focus on the requirements of technical performance In the type of sports effectiveness, privacy in training is one of the basic laws governing the training process in achieving its goal, which is the high level of achievement and the use of modern educational means in the educational process is effective in reaching better learning with an economy of effort, time and money, especially when using appropriate educational means and the type of skill in terms of its type and characteristics and that the level of performance in tennis in recent years has increased clearly and efforts have doubled The change to the high skill level and speed of performance significantly in the world as tennis is a sport that depends heavily on the factor of speed and type in performance methods and that the skills of ground tennis skills are difficult and complex as well as for many types. And the multiplicity of its uses at one point and most of these skills are classified among open skills whose environment is unexpected, which the coach or teacher must increase the effectiveness of learning by enabling the learner to recognize most of the exciting things that can be faced and it is very important for the human being to learn at an early age as it is the basis of sports events that relate to mastering the basic skills of each sporting event, which was the interest of most specialists in the use of modern educational means In terms of the use of ball rackets suitable for age groups as there are no rules specifying the size of the tennis racket, it is different and varied, although all rackets, approximately one length (68cm) and weigh (397g) in the case of men (369g) in the case of women. The players built in the weight of the right rackets are limited between (200-245g) so the player must be careful when choosing to hit if the light bat needs more strength to repel the ball the ground tennis game contains diverse skills and fast ones basic and derivative and the development of the performance of those skills is largely related to the nature of the possibilities and mental abilities derived from the general physical qualities of the tennis game and to offer good results in the level of skill performance and according to interest With the educational and training tools of the game and according to the style of the coach or teacher in accordance with the physical abilities of each player and the age groups in question we have to find an educational tool that contributes effectively to learning some tennis skills and the specificity of the game using tools determined by certain weights and sizes such as balls and strike in addition to the requirements of the other player the researcher was satisfied to delve into one of the important problems that the player is exposed to within the ground tennis The specific age group is researching to find out what many specialists in the game are about the appropriate weight of the player’s physical measurements time implicitly the mass of the arm used carrying the bat (fiercearm) in accordance with the weight of the bat and not the use of educational means and tools arbitrarily, may be to know the direct effect of the mass of the fierce arm and according to the weight of the bat in order to improve the performance of the players and learn them for some basic tennis skills. With small ages in order to increase the effectiveness of learning and increase the accuracy of the performance of skills and development and development of his level of learning and mastery of skill.